Microglial Exosomes in Neurodegenerative Disease - Guo, Min; Hao, Yining; Feng, Yiwei; Li, Haiqing; Mao, Yiting; Dong, Qiang; Cui, Mei (Frontiers in Molecular Neuroscience, 2021)
Microglia play an important role in neurodegenerative disease [i.e., Parkinson’s disease (PD), Alzheimer’s disease (AD), and amyotrophic lateral sclerosis (ALS)]. These diseases share some similar pathological changes and several microglia-associated processes, including immune response, neuroinflammation, phagocytosis, elimination of synapses et al. Microglia in the central nervous system (CNS) has been described as having both destructive and protective effects in neurological disorders. Besides, considerable evidence also indicates that microglia play a significant role in neurogenesis, neuronal cell death, and synaptic interactions. The communication between microglia and neurons is of vital role in regulating complex functions which are key to appropriate the activity of the brain. Accumulating studies have also demonstrated that exosomes with sizes ranging from 40–100 nm, released by microglia, could serve as key mediators in intercellular signaling. These exosomes, identified in terms of cellular origin in many kinds of biological fluids, exert their effects by delivering specific cargos such as proteins, microRNAs (miRNAs), and mRNAs. It was shown that microglial exosomes could transport to and be uptake by neurons, which may either be beneficial or instead, detrimental to CNS diseases. The focus of this review is to summarize the involvement of microglial exosomes in critical pathologies associated with neurodegenerative disease and how they contribute to these disorders, including PD, AD, and ALS. We also review the application of microglia exosomes as potential biomarkers in monitoring disease progression, as well as focusing on their roles as drug delivery vehicles in treating neurodegenerative disorders.